Presenting a Model of Factors Affecting The Development of Medical Tourism in Iran - Nasrollahi, Mahdi; Maleki, Mohammad Hasan; Mohammadi, Zahra (Journal of Foresight and Health Governance, 2025)
This study aims to identify and systematically model the principal factors influencing the development of medical tourism in Iran, and to propose actionable strategies for its enhancement. The present study is applied. The theoretical population of this study includes experts with qualifications and experience in medical tourism. Sampling in this study was done in a judgmental manner and based on specialized knowledge with a sample size of ten people. Literature review, screening questionnaires, and interaction questionnaires were the main data collection methods in this study. Thirty factors were extracted from the research background and expert opinion, of which 21 factors had a defuzzified number greater than 0.7, which were categorized into 9 groups and selected for final evaluation and modeling. The screened stimuli were evaluated using the interaction technique with Micmac software. Four dominant factors were identified as particularly influential in advancing medical tourism in Iran: travel and treatment costs; the influence of the destination country’s culture, religion, and national brand image; the quality of doctors, hospitals, and medical services; and government policies and support. The interactions between these drivers were mapped, providing an in-depth understanding of their systemic roles within the sector. Enhancing the competitiveness of Iran’s medical tourism sector requires strategic measures focused on reducing costs, strengthening national branding and cultural appeal, elevating service quality, and reinforcing government support and policies. The findings offer a robust, data-driven framework for policymakers and sector stakeholders to guide targeted interventions and informed decision making for sustainable development.